Bumblebee size polymorphism and worker response to queen pheromone - Holman, Luke (PeerJ Inc., 2014)
Queen pheromones are chemical signals produced by reproductive individuals in social insect colonies. In many species they are key to the maintenance of reproductive division of labor, with workers beginning to reproduce individually once the queen pheromone disappears. Recently, a queen pheromone that negatively affects worker fecundity was discovered in the bumblebee Bombus terrestris, presenting an exciting opportunity for comparisons with analogous queen pheromones in independently-evolved eusocial lineages such as honey bees, ants, wasps and termites. I set out to replicate this discovery and verify its reproducibility. Using blind, controlled experiments, I found that n-pentacosane (C(25)) does indeed negatively affect worker ovary development. Moreover, the pheromone affects both large and small workers, and applies to workers from large, mature colonies as well as young colonies. Given that C(25) is readily available and that bumblebees are popular study organisms, I hope that this replication will encourage other researchers to tackle the many research questions enabled by the discovery of a queen pheromone.